CONSTRAINING THE EQUATION OF STATE OF FLUID H2O TO 80 GPA USING THE MELTING CURVE, BULK MODULUS, AND THERMAL EXPANSIVITY OF ICE VII - Frank M.R.; Fei Y.; Hu J. (My University, 2004)
The study presented here sought to determine the PVT properties of Ice VII at elevated temperatures and pressures up to 60 GPa using a Mao-Bell type diamond anvil cell with an external Mo-wire resistance heater. The unit cells of Ice VII and gold were monitored during the experiment with gold being used as an internal pressure calibrant. Additionally, the melting curve of Ice VII was determined to greater than 40 GPa by using the disappearance of the diffraction pattern of Ice VII to monitor melting in the system. The melting curve for Ice VII from 3 to 60 GPa was found to be accurately related by a Simon equation: where pressure and temperature are denoted by P (GPa) and T (kelvin), respectively.These results were used further to constrain the PVT properties of fluid H2O at elevated pressures and temperatures by taking the pressure derivative of the Gibbs free energy difference between Ice VII and fluid H2O along the Ice VII melting curve. Comparison of these results suggests that the previously stated equations of state of fluid H2O overestimate the molar volume of fluid H2O at pressures greater than 20 GPa. Although the data presented in this study is not enough to provide an independent EOS for fluid H2O, future work should take account of our data.